Vitamin D Supplementation Improves Pathological Complete Response in Breast Cancer Patients Undergoing Neoadjuvant Chemotherapy: A Randomized Clinical Trial - Omodei, Michelle Sako [UNESP]; Chimicoviaki, Jackeline [UNESP]; Buttros, Daniel Araujo Brito [UNESP]; Almeida Filho, Benedito De Sousa; Carvalho-Pessoa, Carla Priscila [UNESP]; Carvalho-Pessoa, Eduardo [UNESP]; Vespoli, Heloisa Maria De Luca; Nahas, Eliana Aguiar Petri [UNESP] (Taylor & Francis, 2025)
This study aimed to evaluate the effect of vitamin D (VD) supplementation on the pathological complete response (pCR) rate in women with breast cancer (BC) undergoing neoadjuvant chemotherapy (NCT). A randomized clinical trial was conducted with 80 women aged ≥45years with BC who were eligible for NCT. Women were randomized into two groups: VD group, daily supplementation with 2,000IU of cholecalciferol (n = 40) or placebo (n = 40), for 6 months. The primary outcome measure was the pCR rate. Serum 25-hydroxyvitamin-D [25(OH)D] levels were measured after BC diagnosis and the end of NCT. Of the 80 randomized women, 75 completed the NCT and underwent surgery. Baseline 25(OH)D values indicated hypovitaminosis D in both groups (VD: 19.6 ± 5.8 ng/mL and placebo: 21 ± 7.9 ng/mL, p = 0.33). After 6 months, 25(OH)D levels increased in the VD group compared to the placebo group (28 ± 8.7 vs. 20.2 ± 6.1 ng/mL, p = 0.03). The pCR rate was higher in women supplemented with VD when compared than the placebo (43% vs. 24%, p = 0.04). Adjusted logistic regression showed that women with 25(OH)D levels ≥20ng/mL were more likely to achieve pCR (OR3.65, 95%CI 1.09-12.8, p = 0.04). Women with BC undergoing NCT who received supplementation with 2,000IU of VD were more likely to achieve a pathological complete response than women in the placebo group. TRIAL REGISTRATION: Ensaiosclinicos.gov.br, identifier RBR-10k4gqdg.